The Efficiency Of A Depressed Gully Inlet Of A Malaysian Drain - Farouk, Mohamad Zulhilmi (Universiti Sains Malaysia, 2017)
This study was conducted to study the effect of depression on the efficiency of a gully inlet of a Malaysian drain. Stormwater inlets or gullies are designed to collect rainfall runoff before it is drained into a storm drainage system. Usually, the design of gullies is small, vertical and often placed next to street curbs and road intersections. The objective of this study is to determine the efficiency on the hydraulic performance of a gully system with different longitudinal bed slope and cross slope under different flow conditions in order to determine the head-discharge relationship of the grates used. Therefore, a full scale physical model comprising of a testing platform with an inlet tank and an outlet tank on both ends of the platform has been designed to reflect the hydraulic interaction of the gully inlets and the designated catchment area. In this study, two types of systems were tested which were intermediate and terminal. The intermediate condition is a condition, which allows some of the approaching flow to flow past the system into the next downstream gully, while for the terminal condition there is no any significant amount of flow to pass through. The results obtained from the tests are presented in the form of head-discharge relationship and the efficiency of the grates were established.